Optimal trajectory design for the identification of robot and load dynamics - Kozłowski, Krzysztof (1951-2021); Dutkiewicz, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we discuss the issue of the optimal trajectory design for the purpose of identification of the inertial and load parameters of a robot. Two dynamical models have been introduced: differential and integral; both of them can be used to estimate the robot dynamic parameters in which they appear to be linear.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka